The Attention-Information Trade-Off - Serra-Garcia, Marta (American Economic Review, 2026)
How does information transmission change when it requires attracting the attention of receivers? This paper combines an experiment that varies freelance professionals’ incentives to attract attention about scientific findings, with several online experiments that exogenously expose receivers to the content created. Attention incentives lead to significantly less information being transmitted, but not more factually inaccurate content. These incentives increase information demand and the knowledge of interested receivers. However, among the majority of receivers who do not demand more information, attention incentives lower knowledge and increase biases in beliefs, revealing that missing information can be a channel through which misperceptions arise.